Social Media Marketing in the Yorùbá Video Film Industry - Olagoke Alamu (Yoruba Studies Review)
The thrust of this paper is the critical evaluation of the level of acceptance of social media marketing in the Yorùbá film industry. In this age of globalization, many film marketers across the world have abandoned traditional media in favor of online forms of communication, which enable them to share information and get feedbacks from their audience. Based on this premise, it is necessary to investigate the level of acceptance of social media as a channel for film marketing in the fledgling Yorùbá video film industry. Questionnaires were administered to fifty randomly selected marketers in Ibadan and the Lagos metropolis, where there is a high concentration of these video film personnel. The study reveals that due to technology deficiency and lack of interest many marketers have not adopted social media for marketing their film products. The ineffective implementation of the copyright law in Nigeria, which is the major bane of this industry, has also prevented the marketers from adopting the new media. The loose market structure in the industry also deters marketers from maximally utilizing the great potentials social media marketing offers. Recommendations are made for improvement.